Crossing Boundaries: Rethinking the ways that first-in-family students navigate ‘barriers’ to higher education - O'Shea, Sarah (Taylor & Francis, 2020)
This article explores how one cohort of first-in-family students narrated their movement into and through university, proposed as a form of boundary crossing. These metaphors emerged from the stories that students told about their persistence, with references ranging from institutional or organisational boundaries through to those imposed by self and others. Applying the sensitizing lens of boundary crossing, an analysis is provided of how learners navigated their transition into university and the types of persistence behaviours adopted. The focus is on those who traversed these boundaries, considering the nature of incursions and the ways these were negotiated within students’ everyday lives. This cohort all self-identified as being the first in their family to attend university but also acknowledged a variety of additional social, cultural and economic factors that impacted upon their educational journey.